EXPOSURE DAN PENGGUNAAN ALAT ORTODONTI CEKAT PADA KASUS IMPAKSI KANINUS ATAS PADA ANAK (LAPORAN KASUS) - Hendri Fayol; Ismu Suharsono Suwelo (Faculty of Dentistry, Universitas Indonesia, 2015)
Impaction of the permanent maxillary canine is a relative common problem in orthodontic and pedodontic practice. The diagnostic of canin impaction depends upon thorough understanding of clinical and radiological examination. There are several apporaches available for the treatment of these cases. Combination of surgical intervention and orthodontic treatment is one of the choices. The purpose of this case report is to present a case management of a maxillary permanent canine impaction located in the labial surface with vertical position in an 11 years old child. This impacted teeth was brought into the normal position by a combination of surgery and fixed orthodontic treatment.